1996
DOI: 10.1073/pnas.93.26.15215
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E, a redundant cyclin in breast cancer

Abstract: Cyclin E is an important regulator of cell cycle progression that together with cyclin-dependent kinase (cdk) 2 is crucial for the G 1 ͞S transition during the mammalian cell cycle. Previously, we showed that severe overexpression of cyclin E protein in tumor cells and tissues results in the appearance of lower molecular weight isoforms of cyclin E, which together with cdk2 can form a kinase complex active throughout the cell cycle. In this study, we report that one of the substrates of this constitutively act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 49 publications
10
75
0
Order By: Relevance
“…5,[24][25][26][27] We showed that CCNE1 and CCNE2 were both associated with RFI in a univariate analysis, whereas CCNE2 was the only significant variable in the multivariate model. However, when CCNE2 was discarded, CCNE1 became significant.…”
Section: Discussionmentioning
confidence: 87%
“…5,[24][25][26][27] We showed that CCNE1 and CCNE2 were both associated with RFI in a univariate analysis, whereas CCNE2 was the only significant variable in the multivariate model. However, when CCNE2 was discarded, CCNE1 became significant.…”
Section: Discussionmentioning
confidence: 87%
“…While these are as yet unidenti®ed, likely candidates with demonstrated cyclin E-Cdk2 binding ability include known and potential substrates such as the pRB-related proteins p107 and p130, E2F, adaptor proteins like the p300 transcriptional coactivator, or homologues of suc1-CKS family of CDK binding proteins (Parge et al, 1993;La Thangue, 1994;Sidle et al, 1996;Perkins et al, 1997). Indeed, p107 and E2F are complexed to the overexpressed cyclin E protein in the MDA-MB-157 cell line (Gray-Bablin et al, 1996). Furthermore, recent data from this laboratory indicate that the very high molecular weight, active cyclin ECdk2 complexes in oestrogen-stimulated MCF-7 cells contain p130 (Prall, Rogan, Musgrove, Watts and Sutherland, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…non-CDK bound) cyclin D1. This cell line overexpresses p16, which likely competed with cyclin D1 for Cdk4, thus preventing cyclin D1-Cdk4 complex formation (Musgrove et al, 1995;Gray-Bablin et al, 1996). MDA-MB-134 cells displayed a very broad distribution of cyclin D1 protein across the fractions, including some of apparent molecular mass 4100 kDa indicating that some of the overexpressed protein is free in this cell line.…”
Section: Gel ®Ltration Chromatography Separates Active and Inactive Cmentioning
confidence: 94%
“…Precise temporal control of these activities is crucial in establishing transitions from one cell cycle phase to the next and in ensuring that cell cycle events are maintained in the correct order. Uncoupling of Cdk activity from cell cycle progression frequently results in genomic instability and aneuploidy, uncoupling of chromosome replication from segregation or uncontrolled cell proliferation (Gray-Bablin et al, 1996;Mumberg et al, 1996;Haas et al, 1997;Nielsen et al, 1997;Spruck et al, 1999;Harwell et al, 2000). In metazoans, more than one Cdk-cyclin complex is generally required for the transition from one phase to the next.…”
Section: Introductionmentioning
confidence: 99%